Serviço social e meio ambiente: a contribuição do Assistente Social em Programa de Aceleração do Crescimento - PAC - Moreira, Inês da Silva [UNESP] (2013)
The unveiling of reality that permeates the current movements in the global world, and of course in Brazil, indicates the paradigms disrupt and restricted looks on variables entrenchment in the constitution of a more equitable society, with decent living standards and active participation in movements seeking sustainability of their rights. Also, the social expectation back in the sense of being worthy of the efforts of multidisciplinary teams, where the dialogue between different professionals is able to focus their participation in the country's democratic life and honorably citizenship. The role of the Social Service professional in the country's different spheres, shows up founding with teaming formation focused on projects of a socio-economic and environmental basis. The question asked and which is the thesis hypothesis to be proven is if the Social Worker is contributing, in a differently and positive way, in social and educational activities for the restoration and preservation of the environment in the Social Technical Work Project (PTTS in portuguese) - Water Supply from PAC (Growth Acceleration Program). The thesis research was applied in Sumaré in the state of São Paulo, in the period 2008-2011 and is emblematic to give meaning to the statement, confirming it through interviewed subject's speech that comprise one of the sanitation projects, focused on distribution of treated water to the population of the outskirts of the city. Three theoretical axis were used and several authors were visited, in order to show the wide spectrum of potential activities of the social worker, as an differential actor in the categories of growth and development, the reification of the sustainability meaning and social commitment in it and, of intervention actions, especially educational, which the professional is qualified to perform. In terms of methodology, the research is characterized as exploratory, qualitative, bibliographical and...